Noninvasive evaluation of IgA nephropathy fibrosis using Doppler ultrasound. Issue 1 (31st December 2022) - Qin, Xiachuan; Zhang, Chaoxue
Abstract: In this study, we aimed to explore the clinical value of routine color ultrasound parameters in the evaluation of tubular atrophy and interstitial fibrosis (TA/IF) in IgA nephropathy (IgAN). We enrolled 725 patients with IgAN who underwent renal biopsy at the First Affiliated Hospital of Anhui Medical University between January 2019 and May 2022. Examinations were performed to measure the routine ultrasound renal parameters and renal biopsy was done within next three days. Univariate and multivariate analyses were used to determine the correlates and the independent predictors of TA/IF. Simultaneously, a nomogram based on risk indicators was created to predict TA/IF. Univariate and multivariate analyses showed that sex ( p < 0.001, OR = 2.538, 95%CI: 1.739–3.734), renal length ( p < 0.001, OR = 0.927, 95%CI: 0.905–0.95), resistive index of main renal artery ( p = 0.037, OR = 1.891, 95%CI: 1.027–3.426), peak systolic velocity of segmental renal artery ( p = 0.58, OR = 0.975, 95%CI: 0.399–0.841), and cortex echogenicity ( p < 0.001, OR = 3.448, 95%CI: 2.382–5.018) were independent predictors of TA/IF in IgAN nomograms, with a good C -index of 0.765 (95%CI = 0.727–0.803). Analyses of the calibration charts show that nomograms have good performance and clinical applicability. In our study, renal color ultrasound parameters correlated well with TA/IF in IgAN. By establishing a conventional color ultrasound prediction model, we can accurately gauge the extent of TA/IF in patients with IgAN for clinical applications.